Sluggish Cognitive Tempo and Attention Deficit Hyperactivity Disorder: Similarities and Differences - Bolat, Gül Ünsel; Bolat, Hilmi; Özgül, Semiha; Süren, Serkan; Yazıcı, Kemal Utku; Bacanlı, Ali; Ercan, Eyüp Sabri (Galenos Publishing House, 2020)
Objectives: Sluggish cognitive tempo (SCT) is characterized by daydreaming, staring blankly, mental confusion, and hypoactivity. The most important question is how we should evaluate its relationship with the diagnosis of attention deficit hyperactivity disorder (ADHD). Our aim in this study is to determine the behavioral and emotional differences between ADHD and SCT cases. Materials and Methods: The cases included in the study were evaluated using the Atilla Turgay DSM?IV?based child and adolescent disruptive behavioral disorders Screening and Rating scale, child behavior checklist, Barkley child attention survey and teacher rating form. Among 4 groups (145 cases in the only ADHD group, 23 cases in the only SCT gorup, 71 cases in the ADHD + SCT group, 92 cases in the healthy controls), Rating scale scores evaluated by families and teachers were compared. Results: The ADHD group had more symptoms in the evaluation of symptoms of hyperactivity/impulsivity and conduct disorder in both family and teacher scores (p<0.001). In the family assessment, the areas where SCT cases differed significantly were social withdrawal and thought problems, while the areas where ADHD cases differed were somatic problems and delinquent behaviors. In the evaluation of teachers report, the presence of ADHD symptoms was associated with aggressive behavior, somatic problems, social problems, attention problems, and externalizing symptoms were determined. Conclusion: Patients with the symptoms of SCT have difficulties with socially withdrawn and ADHD cases have difficulties in terms of aggression and delinquent behavior problems. The answer to the question of whether or not the reason that the SCT cases show social withdrawal is social phobic features, or reluctance to social communication, or failure to understand social cues will help develop appropriate therapeutic methods. © 2020, Galenos Publishing House. All rights reserved.
Yavaş Bilişsel Tempo ve Dikkat Eksikliği Hiperaktivite Bozukluğu: Benzerlikleri ve Farklılıkları
Keywords: attention deficit hyperactivity disorder; Child Behavior checklist; Sluggish cognitive tempo; social withdrawn